EXPERIMENTAL MODELING AND CONTROL OF A SERVO-HYDRAULIC FORCE CONTROL SYSTEM - Kennedy, Joseph; Fales, Roger (International Journal of Fluid Power, 2010)
The objective of this work is to model a hydraulic force control servo system and then improve upon the performance of the system through feedback control design. The hydraulic system is first constructed and tested. Experimental data based linear models of the system are found through input-output measurements. The models contain a right-halfplane zero; therefore, a bandwidth limitation is placed on the control design (i.e., the bandwidth frequency of the control system is limited). Three types of controllers (P, PID and H∞) are designed specifically for the linear models. The closed-loop time domain and frequency domain performance of each control system is found and compared for the models and system. Uncertainties and performance weights are finally used in finding the nominal/robust stability and performance.